The role of everolimus in malignant bone tumor therapy: Molecular mechanisms, preclinical evidence, and advances in clinical applications - Zhang, Youshu; Dong, Yao; Zhang, Yao; Liang, Gang; Yu, Guanghui; Zhang, Dexiang; Dai, Chuanqiang (Oncology Reviews, 2025)
Malignant bone tumors, particularly osteosarcoma, pose significant therapeutic challenges due to genomic heterogeneity, chemoresistance, and stagnant survival rates. The PI3K/AKT/mTOR pathway emerges as a central driver of tumor progression, metastasis, and therapeutic resistance. Everolimus (EVR), a rapamycin-derived mTORC1 inhibitor, demonstrates multifaceted antitumor effects in osteosarcoma by suppressing protein synthesis, metabolic reprogramming, angiogenesis, and osteoclastogenesis. Preclinical studies highlight EVR’s synergistic potential with targeted agents (e.g., sorafenib, zoledronic acid), chemotherapy (e.g., doxorubicin), and proteasome inhibitors (e.g., bortezomib), achieving >50% tumor volume reduction and metastasis suppression in xenograft models through dual mTORC1/2 blockade, stress-apoptosis activation, and microenvironment remodeling. Clinically, phase II trials report a 45% 6-month progression-free survival (PFS) rate for EVR-sorafenib combinations in refractory osteosarcoma, albeit with manageable toxicity. Precision oncology approaches, such as EVR combined with tumor-treating fields (TTFields) and immune checkpoint inhibitors, further reveal its role in DNA repair-deficient subtypes and TME modulation. However, challenges persist, including mTORC2-mediated resistance, limited intratumoral bioavailability (<20% plasma levels), and biomarker scarcity. Future strategies emphasize bone-targeted nanoparticle delivery systems, dual-target inhibitors (e.g., RapaLink-1), and dynamic multi-omics predictive models to optimize EVR’s precision. By integrating organoid platforms, AI-driven drug screening, and international trials, EVR is poised to evolve from a broad-spectrum agent into a molecularly guided therapeutic hub, bridging “anti-tumor, bone-protective, and immune-regulatory” mechanisms. This paradigm shift promises to transform osteosarcoma management from empirical combinations to biomarker-driven precision therapy, ultimately improving survival and quality of life for patients.